Risk of second primary malignancy in patients with primary myelofibrosis: a SEER database study. Issue 14 (6th December 2022) - Joshi, Utsav; Bhattarai, Adheesh; Gaire, Suman; Gill, Simrat; Agrawal, Vishakha; Yadav, Sumeet Kumar; Low, Soon Khai; Dhakal, Prajwal; Bhatt, Vijaya Raj; Kouides, Peter A.
Abstract: Prior studies report a greater incidence of second primary malignancy (SPM) among patients with myeloproliferative neoplasms, although the true risk in primary myelofibrosis (PMF) has not been elucidated. We utilized the Surveillance, Epidemiology, and End Results database to evaluate the risk of SPM in PMF patients and analyzed the effects of sociodemographic factors on the risk of SPM. Out of 5273 patients, 385 patients (7.30%) developed SPM. SPM occurred at SIR of 1.95 (95% CI 1.76–2.15) and AER of 149.01 per 10, 000 population. A significantly higher incidence of melanoma (SIR 1.76, 95% CI 1.01–2.86), lymphoma (SIR 3.38, 95% CI 2.28–4.83), and leukemia (SIR 27.19, 95% CI 23.09-31.81) was observed. The risk was significantly higher in patients ≤60 years, males, chemotherapy recipients, within 5 years of PMF diagnosis, and for PMF diagnosed after 2009.